Embracing Digitalization in Tourism: Strategic Approaches for Global Competitiveness in the Digital Economy Era - J, Rhena; Kraugusteeliana, Kraugusteeliana; Hamzar (Indo-Fintech Intellectuals: Journal of Economics and Business, 2024)
The digital economy era has transformed various sectors, including tourism. Digital technology enables companies to operate more efficiently and reach global markets more easily. Digital transformation has become an urgent necessity for the tourism industry to remain competitive. This research aims to explore how a strategic approach to digitalization can be applied by tourism businesses to enhance their global competitiveness in the digital economy era. The research employs a literature review method with a qualitative approach. Data were collected from Google Scholar with publication dates ranging from 2011 to 2024. The study results indicate that digitalization has become imperative for tourism businesses in facing global dynamics in the current digital economy era. More than just the use of information technology, digitalization involves a comprehensive transformation of business processes, from marketing to the tourist experience at destinations. Successful examples of tourism digitalization in Indonesia, such as Wonderful Indonesia and online ticket booking platforms, demonstrate significant potential in enhancing global competitiveness and strengthening the local tourism industry